REGARDING THE ISSUE OF RECOGNITION OF OPERATING INCOME IN THE PROCESS OF SALE OF THE COMPANY'S PRODUCTS - Майстер, Людмила; Гладій, Ірина (SWorldJournal, 2023)
In the article the question of authenticity of estimation of profits and charges is investigational in the process of realization of the prepared products with the aim of determination of financial result of activity of enterprise. The comparative analysi